Soil Taxonomy and Distribution Characteristics of the Permafrost Region in the Qinghai-Tibet Plateau, China - FANG Hong-bing; ZHAO Lin; WU Xiao-dong; ZHAO Yu-guo; ZHAO Yong-hua; HU Guo-jie (Journal of Mountain Science, 2015)
Understanding the soil taxonomy and distribution characteristics of the permafrost region in the Qinghai-Tibet Plateau (QTP) is very important. On the basis of extensive field surveys and experimental analysis, this study carries out soil taxonomic classification of the permafrost region in the QTP. According to Chinese Soil Taxonomy, the soil of the permafrost region in the QTP can be divided into 6 Orders (Histosols, Aridosols, Gleyosols, Isohumosols, Cambosols, Primosols), 11 Suborders, 19 Groups and 24 Subgroups. Cambosols are the dominant soil type in the permafrost region, followed by Aridosols. From the east to the west of the permafrost region in the QTP, the soil type gradually changes from Cambosols to Aridosols, showing a meridional zonality. The eastern region is dominated by Cambosols, with no obvious latitudinal zonality. From the south to the northwest of the western region, the dominance of Aridosols and Cambosols gradually transited to Aridosols, presenting a latitudinal zonality. The soil in the western region shows a poor vertical zonality, while the distribution of suborders of Cambosols in the eastern region shows a more obvious vertical zonality. The result indicates that precipitation and vegetation are the main factors that influence the zonal distribution of soil. The permafrost in the east has some effect on the vertical soil zonality, but the effect is weakened in the west.